A Bridge between Conceptual Frameworks Sciences, Society and Technology Studies - Pisano, Raffaele.; Pisano, Raffaele. (History of Mechanism and Machine Science,, 2015)
This book analyzes scientific problems within the history of physics, engineering, chemistry, astronomy and medicine, correlated with technological applications in the social context. When and how is tension between disciplines explicitly practised? What is the conceptual bridge between science researches and the organization of technological researches in the development of  industrial applications?  The authors explain various ways in which the sciences allowed advanced modelling on the one hand, and the development of new technological ideas on the other hand. An emphasis on the role played by mechanisms, production methods and instruments bestows a benefit on historical and scientific discourse: theories, institutions, universities, schools for engineers, social implications as well.  Scholars from different traditions discuss the emerging style of thinking in methodology and, in theoretical perspective, aim to gather and re-evaluate the current thinking on this subject. It brings together contributions from leading experts in the field, and gives much-needed insight into the subject from a historical point of view. The volume composition makes for absorbing reading for historians, philosophers and scientists.